2017
DOI: 10.3390/molecules22030472
|View full text |Cite
|
Sign up to set email alerts
|

A Flavone Constituent from Myoporum bontioides Induces M-Phase Cell Cycle Arrest of MCF-7 Breast Cancer Cells

Abstract: Myoporum bontioides is a traditional medicinal plant in Asia with various biological activities, including anti-inflammatory and anti-bacterial characteristics. To identify the bioactive constituents from M. bontioides, a newly-identified flavone, 3,4′-dimethoxy-3′,5,7-trihydroxyflavone (compound 1), along with eight known compounds, were investigated in human MCF-7 breast cancer, SCC4 oral cancer, and THP-1 monocytic leukemia cells. Among these compounds, compound 1 exhibited the strongest antiproliferative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Histone deacetylase 4 (HDAC4) plays global roles in the regulation of gene transcription, cell growth, survival and proliferation, and their aberrant expressions or activities contribute to cancer development . Zeng LS revealed that upregulated HDAC4 is associated with higher tumor grade, advanced clinical stage, and poor survival rate in esophageal carcinoma, also they found that HDAC4 promoted proliferation and G1/S cell cycle progression in EC cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylase 4 (HDAC4) plays global roles in the regulation of gene transcription, cell growth, survival and proliferation, and their aberrant expressions or activities contribute to cancer development . Zeng LS revealed that upregulated HDAC4 is associated with higher tumor grade, advanced clinical stage, and poor survival rate in esophageal carcinoma, also they found that HDAC4 promoted proliferation and G1/S cell cycle progression in EC cells .…”
Section: Introductionmentioning
confidence: 99%
“…Histone deacetylase 4 (HDAC4) plays global roles in the regulation of gene transcription, cell growth, survival and proliferation, and their aberrant expressions or activities contribute to cancer development. [5][6][7][8][9][10] Zeng LS revealed that upregulated HDAC4 is associated with higher tumor grade, advanced clinical stage, and poor survival rate in esophageal carcinoma, also they found that HDAC4 promoted proliferation and G1/S cell cycle progression in EC cells. 11 Vallabhapurapu | 4585 SUN aNd QIN SD demonstrated that HDAC4 and its downstream complex maintained repressive chromatin around pro-apoptotic genes Bim and BMF and regulates multiple myeloma (MM) survival and growth.…”
Section: Introductionmentioning
confidence: 99%
“…It grows above the tide lines by the sea and adapts to saline-alkali sand and rocky land, which plays an important role in wind-breaking and sand-fixation, as well as greening the environment [ 23 ]. In China, M. bontioides has been used as a folk medicine for antidermatosis, antipyretic, and antipsychotic [ 24 , 25 , 26 , 27 ]. Previous phytochemical studies have revealed some structurally diverse chemicals from this plant, including sesquiterpenoids, iridoids, monoterpenes, phenylethanoids, and flavonoids, some of which showed important bioactivities [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound has been previously isolated from M. bontioides of Taiwan since 2017 and reported to exhibit MCF-7 cell proliferation. [11] Compound 3 was isolated as slightly yellow amorphous powder. It revealed the pseudomolecular ion peak at m/z 287 [M+H] + in the positive ESI-MS.…”
Section: Structural Characterization Of Isolated Compoundsmentioning
confidence: 99%